Al-Qardh dan Al-Qardhul Hasan sebagai Wujud Pelaksanaan Tanggung Jawab Sosial Perbankan Syariah - Muhammad Imam Purwadi (Jurnal Hukum IUS QUIA IUSTUM, 2014)
The problems discussed in this research are: first, how the responsibility of sharia banking in Indonesia is, and second, the how the development and implementation of legal provision of al-qardh andalqardhul hasanproducts are as the realization of social responsibility of sharia banking to create the social welfare in PT Bank Muamalat Indonesia Tbk. This research is a qualitative study using normative juridical and empirical juridical approaches. The result of the research concludes that: first, corporatesocial responsibilityof sharia banking is defined as an instrument to enhance the work performance and service for the society. The implementation of CSR program varies in forms of assistances for education, health, poverty alleviation, social, religion, infrastructure, and environment, as well as through financing products. Second, in its implementation, there is not a specific provision regulating the implementation of al-qardhandal-qardhul hasanas CSR in sharia banking. PT Bank Muamalat Tbk has not yet formulated the application and implementation of al-qardhandal-qardhul hasanprinciples to realize the social welfare.